Clinical Validation of a Novel T-Cell Receptor Sequencing Assay for Identification of Recent or Prior Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (6th May 2022) - Dalai, Sudeb C; Dines, Jennifer N; Snyder, Thomas M; Gittelman, Rachel M; Eerkes, Tera; Vaney, Pashmi; Howard, Sally; Akers, Kipp; Skewis, Lynell; Monteforte, Anthony; Witte, Pamela R; Wolf, Cristina; et al.
Abstract: Background: While diagnostic, therapeutic, and vaccine development in the coronavirus disease 2019 (COVID-19) pandemic has proceeded at unprecedented speed, critical gaps in our understanding of the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remain unaddressed by current diagnostic strategies. Methods: A statistical classifier for identifying prior SARS-CoV-2 infection was trained using >4000 SARS-CoV-2–associated T-cell receptor (TCR) β sequences identified by comparing 784 cases and 2447 controls from 5 independent cohorts. The T-Detect COVID (Adaptive Biotechnologies) assay applies this classifier to TCR repertoires sequenced from blood samples to yield a binary assessment of past infection. Assay performance was assessed in 2 retrospective (n = 346; n = 69) and 1 prospective cohort (n = 87) to determine positive percent agreement (PPA) and negative percent agreement (NPA). PPA was compared with 2 commercial serology assays, and pathogen cross-reactivity was evaluated. Results: T-Detect COVID demonstrated high PPA in individuals with prior reverse transcription–polymerase chain reaction (RT-PCR)–confirmed SARS-CoV-2 infection (97.1% 15+ days from diagnosis; 94.5% 15+ days from symptom onset), high NPA (∼100%) in presumed or confirmed SARS-CoV-2 negative cases, equivalent or higher PPA than 2 commercial serology tests, and no evidence of pathogen cross-reactivity. Conclusions: T-Detect COVID is a novel T-cell immunosequencing assay demonstrating high clinical performance for identification of recent or prior SARS-CoV-2 infection from blood samples, with implications for clinical management, risk stratification, surveillance, and understanding of protective immunity and long-term sequelae. Abstract : T-Detect™ COVID, a novel T-cell immunosequencing assay, exhibits high positive and negative percent agreement with RT-PCR for identification of prior SARS-CoV-2 infection in blood. Performance was equivalent or better than 2 commercial serology tests, particularly in early phases of infection.